2000
DOI: 10.1002/1099-081x(200001)21:1<23::aid-bdd212>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Effect of food on the pharmacokinetics of osmotic controlled-release methylphenidate HCl in healthy subjects

Abstract: The effect of a high-fat meal on the pharmacokinetics of OROS(R) (methylphenidate HCl), an osmotic controlled-release formulation of methylphenidate HCl, was investigated in healthy subjects. Mean peak methylphenidate plasma concentrations occurred slightly later and peak methylphenidate plasma concentrations and AUC values were slightly higher (approximately 10-30%) in the presence of food than in the absence of food. There was no difference in the plasma elimination half-life of methylphenidate between the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(8 citation statements)
references
References 28 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…This finding was similar to a previous study that found differences of 10-30% for AUC values between the fasted and fed states with Concerta Ò . [73] Also, although not reaching statistical significance, a mean prolongation in T max values of 1.9 and 2.6 hours was observed for the fed (vs fasted) states of Concerta Ò and Adderall XR Ò , respectively. [72] Beaded technologies appear particularly susceptible to pharmacokinetic changes associated with food, whereas the extent of absorption of methylphenidate from the wax-based matrix of Ritalin SR Ò appears to be modestly enhanced when administered with food.…”
Section: Effect Of Food On Pharmacokinetic Parameters Of Stimulant Fomentioning
confidence: 85%
“…This finding was similar to a previous study that found differences of 10-30% for AUC values between the fasted and fed states with Concerta Ò . [73] Also, although not reaching statistical significance, a mean prolongation in T max values of 1.9 and 2.6 hours was observed for the fed (vs fasted) states of Concerta Ò and Adderall XR Ò , respectively. [72] Beaded technologies appear particularly susceptible to pharmacokinetic changes associated with food, whereas the extent of absorption of methylphenidate from the wax-based matrix of Ritalin SR Ò appears to be modestly enhanced when administered with food.…”
Section: Effect Of Food On Pharmacokinetic Parameters Of Stimulant Fomentioning
confidence: 85%
“…The remaining profiles show a continuous increase, which means that drug release from the immediate-release and extended-release phase overlap and cannot be separated by a cut-off; hence the immediate-release and the extended-release phase cannot be adequately characterized using partial pharmacokinetic parameters under fed conditions (Modi et al. 2000 ). The two different types of profiles (biphasic or continuous) under fed conditions are most likely caused by differences in the first site of deposition of the dosage form within the stomach directly after ingestion.…”
Section: Discussionmentioning
confidence: 99%
“…The OROS MPH HCl delivery system contains a drug overcoat of IR MPH (consisting of 22% of the active substance) designed to dissolve shortly after swallowing the capsule, resulting in an initial rapid increase in plasma concentration, and an osmotic release system which provides a gradual increase in plasma concentration that peaks approximately 6 to 8 hours after dosing. The plasma concentration then gradually declines, reaching the baseline values by 24 hours (Modi NB, 2000).…”
Section: Figure 1methylphenidatementioning
confidence: 96%